2015
DOI: 10.1007/s00018-015-1931-1
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalizing intestinal epithelial cell toll-like receptors for immune surveillance

Abstract: SUMMARY Toll-like Receptors (TLRs) are membrane-bound microbial sensors that mediate important host-to-microbe responses. Cell biology aspects of TLR function have been intensively studied in professional immune cells in particular the macrophages and dendritic cells, but not well explored in other specialized epithelial cell types. The adult intestinal epithelial cells are in close contact with trillions of enteric microbes and engage in life long immune surveillance. Mature intestinal epithelial cells, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 123 publications
1
56
1
Order By: Relevance
“…Proteobacteria are gram-negative, LPScarrying, proinflammatory bacteria (57). Bacterial products such as LPS can activate pattern recognition receptors, e.g., Toll-like receptors (TLR), on the apical and basolateral side of intestinal epithelial cells (IECs), leading to cytokine release (66). The proteobacteria Suterella, for example, can trigger IL-8 production from enterocytes (32).…”
Section: Fat Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteobacteria are gram-negative, LPScarrying, proinflammatory bacteria (57). Bacterial products such as LPS can activate pattern recognition receptors, e.g., Toll-like receptors (TLR), on the apical and basolateral side of intestinal epithelial cells (IECs), leading to cytokine release (66). The proteobacteria Suterella, for example, can trigger IL-8 production from enterocytes (32).…”
Section: Fat Contentmentioning
confidence: 99%
“…Dysbiosis is associated with an increase in gram negative bacteria, which produce LPS (20). Increased amounts of LPS in the gut result in TLR4 activation on IEC and release of proinflammatory cytokines (39,66). Tight junction proteins control diffusion and leakage of digestive products between the GI tract and circulatory system.…”
Section: Crucial Role Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…toxins, polyphosphate chains, other compounds still unknown). These sensors include for example Toll-like receptors (TLRs) [2, 3] and receptors to SCFA. All these mechanisms make the molecular basis of the crosstalk between the host and the gut microbiota at the epithelial level.…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that upon being transferred to the cell membrane the receptor is still able to bind its ligands, but fails to relocate NF-B to the nucleus. To effectively evoke proinflammatory signals TLR9 has to be directed to the endolysosomal compartment, where the dimerized receptor is cleaved by cathepsins and endopeptidases (Yu and Gao, 2015). In line with these hypothesis, TLR9-/-mice were shown to suffer from the delayed healing after chemical gut damage (Rose et al, 2012) and TLR9 synthetic agonists were shown to protect from the radiation injury (Saha et al, 2012).…”
Section: Intestinal Epitheliummentioning
confidence: 90%